ESSENTIALS OF MARKETING theory and practice for a marketing career - Brown, David; Thompson, Alexander (ROUTLEDGE, 2022)
This comprehensive textbook introduces students to all the core principles of marketing practice using an employability-focused approach. Essentials of Marketing is underpinned by six pillars, which flow through each chapter: marketing ethics, sustainability, stakeholder engagement, globalisation, the power of new media, and measuring success. The book demystifies theory by placing it in contexts which are recognisable to a diverse readership, using real-life case studies and examples designed to engage today's technologically savvy and internationally oriented students. The book includes a comprehensive running case study in which readers are invited to adopt the roles of marketing assistant, marketing manager, and marketing director within regional markets, applying the knowledge that they have learned in each chapter into modern, realistic contexts, which simulate a marketing career. Key features to aid learning and comprehension include case studies, chapter objectives and summaries, key learning points, and key questions. With a uniquely accessible and applied approach, Essentials of Marketing is designed as a core text for undergraduate and postgraduate students studying Introduction to marketing, marketing management, and principles of marketing modules. Digital learning resources include a comprehensive instructor's manual to guide interaction with the applied case study, PowerPoint slides, and a test bank.
Keywords: Marketing; marketing; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / International / Marketing; BUSINESS & ECONOMICS / E-Commerce / Internet Marketing